RNA interference shapes stress responses in Arabidopsis thaliana - De Meo, Elisa; Baldisseri, Anna; Loreti, Elena; Perata, Pierdomenico (Frontiers in Plant Science, 2025)
RNA interference (RNAi) is a crucial regulatory mechanism in plants, enabling dynamic responses to environmental stresses. Small RNAs (sRNAs), including miRNAs and siRNAs, guide stress-responsive gene silencing and can act beyond the cell of origin through systemic movement and uptake, enhancing plant adaptability. Central to these pathways are ARGONAUTE (AGO) proteins, whose stress-regulated expression and diverse roles at the molecular level contribute to finely tuned responses. This review integrates current progress in sRNAs systemic signaling, stress-responsive RNAi mechanisms, and AGO protein diversity into a coherent framework for understanding RNAi-driven stress adaptation. Emerging approaches such as high-resolution sRNA sequencing and single-cell transcriptomics are now enabling a deeper understanding of RNAi regulation with improved spatial and temporal resolution.